Assessment of investor relations on the Polish exchange market - Nowak, Tomasz; Wysocka, Katarzyna (Ocena relacji inwestorskich na polskim rynku giełdowym, 2020)
Investor relations play a significant role in increasing a company’s value and may contribute to improving its image in the business environment. It is the transparency and reliability of the information provided that affects the trust and willingness of investors to identify with a given company. The purpose of the article is to show the role of investor relations among companies in Poland. An overview of publications in Polish and English was conducted. The essence, goals and the instruments of investor relations were the focus of the study. Only the companies that engage in new technological solutions used by investor relations, e.g. videoconferences, conference calls, teleconferences, Facebook, and Twitter, are successful in the modern capital market. Moreover, a survey was conducted among Polish individual investors. Its results demonstrated what preferences and requirements Polish investors have with regard to information. Moreover, the analysis of the investors’ responses also showed the degree to which Polish stock exchange companies are involved in the communication through new technologies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 160-172
Keywords: investor relations; capital market; investors; IR tools; relacje inwestorskie; rynek kapitałowy; inwestorzy; narzędzia IR